WELCOME TO INCLUSIVE EDUCATION! - Cristian RĂDUCANU (National Centre for Policy and Evaluation in Education, 2017)
This article is dedicated to the specific problems of young Roma who are confronted in schools with a false equality of opportunities in education and a type of positive discrimination which does not help. Starting from the historical, social and economic background of this group, a few personal arguments of the author are expressed, formed on the basis of his long experience in mixed classes of Romanian and Roma pupils. The paper contains a proposal, a few activities applicable to this ethnic group. At the end of the article, the author brings some recommendations for improving the performance of young Roma and the relationship with these youngsters for a pleasant, balanced, relaxed school climate, based on those cultural values understood and accepted by the Roma.